2019
DOI: 10.1002/ejoc.201900315
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐Crown Ethers as Novel Scaffolds for the Development of Al3+‐Selective Fluorescent Probes

Abstract: Herein, we report the systematic evaluation of the BODIPY series functionalized with pseudo‐crown ethers against metal cations and assessment of their potential as novel off‐on fluorescent probes selective for aluminum(III) cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In our recent works we have reported several substitution strategies at the BODIPY core that ultimately allow photochemical and spectral tuning of dyes [11] . Amongst other things we have demonstrated that BODIPYs bearing pendant polyamines and amino alcohols are promising as viscosity sensors [11a,f] and Zn(II)‐selective probes for imaging in plants roots [11e] . In this work, we report an extended series of BODIPYs modified at the 8 position with polyamines and diethanolamines using a methylene spacer, which allows the exploration of the impact of the aza substituent on the dye fluorescence in the presence different cations.…”
Section: Introductionmentioning
confidence: 98%
“…In our recent works we have reported several substitution strategies at the BODIPY core that ultimately allow photochemical and spectral tuning of dyes [11] . Amongst other things we have demonstrated that BODIPYs bearing pendant polyamines and amino alcohols are promising as viscosity sensors [11a,f] and Zn(II)‐selective probes for imaging in plants roots [11e] . In this work, we report an extended series of BODIPYs modified at the 8 position with polyamines and diethanolamines using a methylene spacer, which allows the exploration of the impact of the aza substituent on the dye fluorescence in the presence different cations.…”
Section: Introductionmentioning
confidence: 98%
“…[13][14][15][16][17][18][19] By contrast, significant progress has been achieved in the development and application of fluorescent probes for the selective binding and identification of different metals, exhibiting unique properties including operational simplicity, low cost, high sensitivity and high selectivity. 20,21 Until now, some fluorescent probes for detecting Al 3+ have been reported based on internal charge transfer (ICT), [22][23][24] photoinduced electron transfer (PET), [25][26][27][28][29] chelation-enhanced fluorescence (CHEF), [30][31][32] and fluorescence resonance energy transfer (FRET) mechanisms. 33 However, most of these probes need to be applied in the organic/water mixture for the detection of Al 3+ ; the Al 3+ ion easily dissolves in water medium.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence techniques for detecting various ions have become an optimal choice due to their high sensitivity and selectivity (Suresh et al, 2018;Ye et al, 2019b;Bai et al, 2020;Wu et al, 2020;Zhao et al, 2020). In the past few years, various fluorescent chemosensors including coumarin, naphthalimide, pyrene, BODIPY, anthracene, and rhodamine were exploited for detection of Al 3+ (Samanta et al, 2014;Hossain et al, 2017;Kozlov et al, 2019;Prabhu et al, 2019;Roy et al, 2019;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%